1999
DOI: 10.1038/sj.bjc.6690231
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind trial of beta-carotene and vitamin C in women with minor cervical abnormalities

Abstract: A double-blind, placebo-controlled, randomized, factorial study using a daily oral administration of 30 mg beta-carotene and/or 500 mg vitamin C was conducted in 141 women with colposcopically and histologically confirmed minor squamous atypia or cervical intra-epithelial neoplasia (CIN) I. Over approximately 2 years of follow-up, 43 lesions regressed to normal and 13 progressed to CIN II. The regression rate was slightly higher, but not significantly so, in those randomized to beta-carotene compared to no bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…In a randomized clinical trial investigating the association of b-carotene with early preinvasive lesions, oral administration of b-carotene had no effect on atypical squamous cells of undetermined significance (ASCUS)-CIN1 regression rates during 2 years of follow-up (24). Results from a case-control study by Nagata et al showed an inverse association between serum lycopene concentrations and cervical dysplasia (25).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized clinical trial investigating the association of b-carotene with early preinvasive lesions, oral administration of b-carotene had no effect on atypical squamous cells of undetermined significance (ASCUS)-CIN1 regression rates during 2 years of follow-up (24). Results from a case-control study by Nagata et al showed an inverse association between serum lycopene concentrations and cervical dysplasia (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that the intake of fruits and vegetable has a protective effect against cervical cancer. Many studies on diet and cervical cancer risk have evaluated the nutrient intake rather than the food intake [7][8][9]. However, single foods contain many nutrients, some of which are not measured.…”
Section: Introductionmentioning
confidence: 99%
“…106,107 Early results from uncontrolled trials suggesting that vitamin C and beta carotene were beneficial for cervical cancer were not supported in a properly controlled trial. 112 And, there is no good evidence that taking supplements of vitamins A, C, or E at doses above the DV is associated with any clinical benefit. 113 Despite the many gaps in scientific knowledge about supplements, many cancer survivors take supplements and are eager to learn more about them.…”
Section: Nutrition During and After Cancer Treatmentmentioning
confidence: 99%